OPINIONS OF CANDIDATE TEACHERS ABOUT THE VALUES OF AKHISM OF THE TRADESMEN (KIRSEHIR SAMPLE) - İrem DEMİRBAŞ; Ayfer ŞAHİN (International Journal of Eurasia Social Sciences, 2017)
Akhism; Is a non-governmental organization that aims to bring people together with the nation and to live in a peaceful way and to get the right of the artisans to work in a peaceful way. This study is a case study in which descriptive and quantitative data gathering techniques aimed to determine the opinions of prospective teachers about the values of ahilik that they have in Kırşehir. The sample of the study was formed from 206 teacher candidates who continued to 2nd, 3rd and 4th grade determined by sampling criterion. The data were obtained with the "Ahi Values Scale". In the study, it was determined that the opinions of the prospective teachers about the value of ahirilik which the artisans had learned were moderately positive and partly agree. When the t-test results of the opinion of the prospective teachers about the value of the ahilik value of the tradesmen are examined; It shows a meaningful difference according to sex. When the t-test results of the opinions of the prospective teachers about the value of the mahjong that the artisans possessed are taken into consideration, reading the book and participating in the seminar / conference are examined; It does not show any significant difference. When the results of the one-way analysis of variance for the opinions of the prospective teachers about the values of ahirilik which the tradesmen had were examined, it was determined that they did not show any significant difference compared to the second, third and fourth grade levels.